The Urgency of Regulatory Enforcement of Production and Circulation Laws Alcoholic Drinks (Oplosan Liquor) - Heryawan, Rio Dedy; Budiarsih, Budiarsih; Mangesti, Yovita Arie (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to examine how the The Urgency of Regulatory Enforcement of Production and Circulation Laws Alcoholic Drinks (Oplosan Liquor). The type of research method used in writing this thesis proposal is a normative juridical method by conducting a literature study on legal materials, both primary legal materials, namely related legislation and secondary legal materials, namely literature related to the topic of the problem. Based on the results of normative research on the enforcement of the production and distribution of alcoholic beverages (alcoholic liquor) urgent for the regulation in law enforcement. This is due to the philosophical reason that intoxicating alcoholic beverages for most religions and certain ethnicities is believed to be prohibited behavior, and requires the existence of laws that provide certainty.